ADSORPTION OF LAUNDRY WASTEWATER POLLUTANS WITH A MIXTURE OF PDAM SLUDGE AND DURIAN PEEL ADSORBENT (Durio Zibethinus) - Ibrahim, ibrahim; waryati, waryati; rahayu, dwi ermawati; Tamrin, Tamrin; Aditya, Rizki Andri Ahmad (Universitas Mulawarman, 2025)
High levels of phosphates and surfactants will cause rapid organism growth, which can lead to dissolved oxygen depletion, reduce water environment quality, and be harmful to biota. One of the treatments that can be performed to process laundry wastewater is the adsorption process. The wastewater treatment conducted in this study uses adsorbents from durian peels and PDAM sludge. Research about the adsorbents is related to the carbonization temperature, chemical activator, stirring speed, and contact time of the adsorbents with the laundry wastewater. This study aims to determine the effectiveness of durian peel adsorbent, PDAM sludge, and a mixture both of adsorbents . The adsorbents that have been made were tested for characteristics such as moisture content, ash content, volatile matter, pure carbon, iodine absorption, surface area, and specific pores. The variations used were contact times of 15, 30, 45, and 60 minutes and types of adsorbents: durian peel, PDAM sludge, and a mixture both of adsorbents. The results showed that durian skin and PDAM sludge adsorbents meet the SNI 06-3730-1995 adsorbent characteristics, except that iodine absorption did not meet. The most effective contact time of durian peel adsorbent in reducing phosphate and surfactant levels was 15 minutes. The most effective contact time of PDAM sludge adsorbent and a mixture of the two adsorbent in reducing phosphate levels is 15 minutes, and for surfactant, it is 45 minutes. Further research that can be done is to make adsorbents at different temperatures from this study.